Metastatic pattern and new primary tumours after neoadjuvant therapy and surgery in rectal cancer. (11th October 2018) - Frambach, P.; Pucciarelli, S.; Perin, A.; Zuin, M.; Toppan, P.; Maretto, I.; Urso, E. D. L.; Spolverato, G.
Abstract: Aim: Current follow‐up guidelines for distant tumour recurrence after rectal cancer surgery are not defined or agreed. The aim was to elucidate the pattern of recurrence over time and provide information that could help direct a strategy for surveillance. Method: In all, 378 patients with locally advanced rectal cancer were treated with preoperative chemoradiotherapy and surgery with curative intent. Patients were followed up with a standard protocol, and data were prospectively collected in a dedicated database. Disease‐free survival and overall survival were calculated. Results: Within a median follow‐up time of 75 months, rates of local and distant recurrence were 2.6% and 21.7%, respectively. Risk factors for recurrence were a baseline carcinoembryonic antigen > 5.0 ng/ml, a distance from the anal verge ≤ 5 cm, R1 resection margins, G3 grading, ypT staging > 2, positive lymph node status and a tumour regression grade of 3–5. Disease‐free survival did not vary significantly between patients with lung and extra‐pulmonary metastases ( P = 0.59). The only factor associated with increased risk of lung metastases was a distance of the tumour from the anal verge of ≤ 5 cm ( P = 0.01). Most recurrences occurred within the first 3 years after surgery (74.4%). The first site of recurrence was most frequently the lung (52.0%). The most frequent new primary malignancy was lung cancer (22.5%). Conclusions: Patients undergoing curative therapy for rectal cancer often experience distant recurrence; the majority of recurrences occur within the first 3 years after surgery and lung metastases are the most common. A predictive factor for pulmonary recurrence is a tumour in the lower rectum.